Projected Range Dependent Tunneling Current of Asymmetric Double Gate MOSFET - Hak Kee Jung (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This study is to analyze the changes of tunneling current according to projected range, a variable of Gaussian function of channel doping function of Asymmetric Double Gate; ADG MOSFET. In MOSFET with channel length below 10 nm, tunneling current occupies a large percentage among off-currents. The increase of tunneling current has a large effect on the characteristics of subthreshold such as threshold voltage movement and the decline of subthreshold swing value, so the accurate analysis of this is being required. To analyze this, potential distribution of series form was obtained using Gaussian distribution function, and using this hermeneutic potential distribution, thermionic emission current and tunneling current making up off-current were obtained. At this point, the effect that the changes of projected range, a variable of Gaussian distribution function, have on the ratio of tunneling current among off-currents was analyzed. As a result, the smaller projected range was, the lower the ratio of tunneling current was. When projected range increased, tunneling current increased largely. Also, it was observed that the value of projected range which the ratio of tunneling current increased changed according to maximum channel doping value, channel length, and channel width.